The Values of Pancasila as a Pillar of National Life in the Modern Era - Raka Agustian Setyo Nugroho; Juzidane S. M (Konsultan Jurnal Ilmiah Indonesia, 2026)
This research is based on the important values ​​of Pancasila as the foundation of the state and the Indonesian people's way of life, which must continue to function in the era of modernization and globalization. The principles of Pancasila serve as moral norms and national characteristics that maintain unity amidst social and cultural diversity and face the influence of technology and digitalization. The purpose of this research is to analyze the role and significance of Pancasila values ​​as the moral foundation and national identity, while also identifying challenges and opportunities in their implementation, especially among young people. The approach used in this research is qualitative, conducting a literature review from various scientific sources, especially indexed national journals that discuss Pancasila values ​​as pillars of national life in the modern era. Data collection was conducted through a Google Scholar search and analysis of relevant literature. The findings of the study indicate that Pancasila values, such as divinity, humanity, unity, democracy, and social justice, serve as a strong foundation for building national commitment and national character. The application of these values ​​in everyday life, including in formal and informal education, is crucial as a reference in formulating inclusive public policies. With this, it can be concluded that Pancasila remains relevant as a foundation for social and state life, strengthening social unity and national resilience, and acting as a shield against global challenges and social disintegration.